Anti-vulcanizing rubber and products containing metal.
Patent Information
- Application Number
- TW114104729
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2026-08-16
- Estimated Expiration
- 2045-02-07
AI Technical Summary
Existing commercial conformal adhesives lack resistance to corrosive substances like sulfur and sulfides, leaving metal circuits in electronic devices vulnerable to corrosion.
An anti-vulcanization adhesive comprising a (meth)acrylate polymer with silicate groups and 0.5 wt% to 5 wt% benzotriazole molecules with silicate groups, which provides excellent anti-sulfurization and salt spray resistance.
The adhesive effectively protects metal components from corrosion in sulfur-containing and saline environments, offering moisture, dust, chemical, and sulfidation protection with good adhesion and salt spray resistance.
Abstract
Description
[Technical Field]
[0001] This invention relates to a material for surface treatment, and more particularly to an anti-vulcanization adhesive. [Previous Technology]
[0002] In the past, to prevent corrosion of the metal circuits of electronic devices, conformal adhesives with moisture-proof, dust-proof, and chemical-resistant properties were often applied to the metal circuits to form a barrier layer, protecting the metal circuits from environmental corrosion and thus extending the lifespan of the electronic devices. However, currently available commercial conformal adhesives lack resistance to corrosive substances such as sulfur, mercaptans, or sulfides (e.g., hydrogen sulfide), leaving the metal circuits still at risk of corrosion.
[0003] To address the above-mentioned problems, US Patent Publication No. 2004219785 discloses a coating for preventing the sulfidation of metal plates, wherein the coating comprises a (meth)acrylic resin having hydrolyzable silyl groups and / or silanol groups and a volatile solvent. The (meth)acrylic resin is formed by polymerization of a component comprising an unsaturated silane compound having polymerizable double bonds and hydrolyzable silyl groups and methyl methacrylate. The silicon atom content in the (meth)acrylic resin is 0.1 wt% to 5 wt%, and the weight average molecular weight is 1500 to 30000. Although this coating can prevent the sulfidation of metal plates, experiments have shown that the degree of sulfidation prevention is still unsatisfactory. [Summary of the Invention]
[0004] Therefore, one object of the present invention is to provide an anti-vulcanization adhesive.
[0005] Therefore, the anti-vulcanization adhesive of the present invention comprises a (meth)acrylate polymer having a silicate group and 0.5 wt% to 5 wt% of a benzotriazole molecule having a silicate group.
[0006] The silica-containing (meth)acrylate polymer is formed by polymerization of a reaction mixture, and the reaction mixture comprises a (meth)acrylate component and a thermal initiator. The (meth)acrylate component comprises a silicate monomer and 80 wt% to less than 100 wt% of an alkyl (meth)acrylate. The amount of the thermal initiator is 0.05 wt% to 1.0 wt% based on a total reaction mixture of 100 wt%.
[0007] Another object of the present invention is to provide an article having a metal component.
[0008] The present invention comprises a metal article, including a metal component and a sulfur-resistant component disposed on the metal component, wherein the sulfur-resistant component is formed of a component including the above-mentioned sulfur-resistant adhesive.
[0009] The advantages of this invention are as follows: Through the above-mentioned component design, especially the benzotriazole molecules with siloxy groups, the anti-sulfurization adhesive formed by this invention has excellent anti-sulfurization ability, enabling metal components to avoid corrosion due to the presence of sulfur when used in sulfur-containing environments. Simultaneously, the anti-sulfurization adhesive formed by this invention also has excellent salt spray resistance, enabling the metal components to avoid corrosion due to the presence of salt when used in saline environments, such as marine, coastal areas, or other high-salt environments.
Implementation Method
[0010] The present invention will now be described in detail.
[0011] The anti-vulcanization adhesive of the present invention comprises a (meth)acrylate polymer having a silicate group and 0.5wt% to 5wt% of a benzotriazole molecule having a silicate group.
[0012] <Silyl-containing (meth)acrylate polymers>
[0013] The silica-based (meth)acrylate polymer is formed by polymerization of a reaction mixture. The reaction mixture comprises a (meth)acrylate component and a thermal initiator. The amount of the thermal initiator is from 0.05 wt% to 1.0 wt%, based on a total reaction mixture of 100 wt%. In some embodiments, the viscosity of the silica-based (meth)acrylate polymer is from 200,000 cp to 400,000 cp. In some embodiments, the weight-average molecular weight (Mw) of the silica-based (meth)acrylate polymer is from 100,000 to 300,000. In some embodiments, the weight-average molecular weight (Mw) of the silica-based (meth)acrylate polymer is from 170,000 to 185,000. In some embodiments, the glass transition temperature of the silica-based (meth)acrylate polymer is from 50°C to 110°C. In some embodiments, the glass transition temperature of the silica-based (meth)acrylate polymer is 100°C to 110°C.
[0014] [(Meth)acrylate component]
[0015] The (meth)acrylate component includes a silicate monomer and an alkyl (meth)acrylate, and the amount of the alkyl (meth)acrylate is 80 wt% or more and less than 100 wt%, based on the total amount of the (meth)acrylate component being 100 wt%.
[0016] In some embodiments of the present invention, the total amount of the siloxane monomer is 100 wt%, and the content of the silicon atoms is 0.1 wt% to 5 wt%. The siloxane monomer can be used alone or in combination. In some embodiments of the present invention, the siloxane monomer is, for example, but not limited to, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, dimethoxymethylvinylsilane, diethoxymethylvinylsilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, or 3-methacryloxypropylmethyldiethoxysilane, etc. In some embodiments of the present invention, the amount of alkyl methacrylate is 80 wt% to 95 wt%, based on a total amount of 100 wt% of the (meth)acrylate component.
[0017] In some embodiments of the present invention, the (meth)acrylate alkyl ester is, for example, but not limited to, methyl methacrylate.
[0018] To give the anti-vulcanization adhesive water-repellent and / or oil-repellent properties, in some embodiments of the present invention, the (meth)acrylate component further includes a fluorinated alkyl (meth)acrylate. The fluorinated alkyl (meth)acrylate can be used alone or in combination. Examples of the fluorinated alkyl (meth)acrylate include, but are not limited to, dodecafluoroheptyl acrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl acrylate, tridecafluorooctyl methacrylate, heptadecafluorodecyl acrylate, or heptadecafluorodecyl methacrylate. In some embodiments of the present invention, based on a total (meth)acrylate component of 100 wt%, the amount of the fluorinated alkyl (meth)acrylate is greater than 0 wt% and less than 15 wt%.
[0019] [Thermal Initiator]
[0020] The thermal initiator can be used alone or in combination with other agents. In some embodiments of the invention, the thermal initiator is, for example, but not limited to, an azo compound or a peroxide. The azo compound is, for example, but not limited to, 2,2'-azobis(isobutyronitrile) or 2,2'-azobis(2,4-dimethylpentanonitrile). The peroxide is, for example, but not limited to, benzoyl peroxide or lauryl peroxide. In some embodiments, the amount of the thermal initiator is 0.05 wt% to 0.2 wt% based on a total reaction mixture of 100 wt%.
[0021] [Chain transfer agent]
[0022] In some embodiments, the reaction mixture further comprises a chain transfer agent. This chain transfer agent may be used alone or in combination. In some embodiments of the invention, the chain transfer agent is, for example, but not limited to, a thiol-based chain transfer agent or an α-methyl styrene dimer. The thiol-based chain transfer agent is, for example, but not limited to, n-dodecanethiol, sec-dodecyl mercaptan, tert-dodecanethiol or tert-dodecyl mercaptan, mercaptoethanol, or mercaptoacetic acid. The α-methyl styrene dimer is, for example, but not limited to, a linear α-methyl styrene dimer or an α-methyl styrene cyclic dimer. The linear α-methyl styrene dimer is, for example, but not limited to, 2,4-diphenyl-4-methyl-1-pentene or 2,4-diphenyl-4-methyl-2-pentene. The α-methylstyrene cyclic dimer is, for example, but not limited to, 1,1,3-trimethyl-3-phenylindane. In some embodiments, the amount of the chain transfer agent is greater than 0 wt% and less than 0.5 wt% based on a total reaction mixture of 100 wt%. In some embodiments, the amount of the chain transfer agent is greater than 0 wt% and less than 0.1 wt% based on a total reaction mixture of 100 wt%.
[0023] <Benzotriazole molecules with siloxy groups>
[0024] The benzotriazole molecule having a silicaloxy group can be used alone or in combination. In some embodiments of the present invention, the benzotriazole molecule having a silicaloxy group is, for example, but not limited to, R1, R2, R3, and R4 being independently hydrogen, alkyl, or alkyl; Y represents hydrogen or alkyl; L is a group having an aminocarbamate group [-OC(O)-N-], an ester group [-OC(O)-], or an amino group [-C(O)-N-]; T1 to T3 are independently hydrogen or alkoxy; T1 to T3 are not simultaneously hydrogen; n represents an integer greater than or equal to 1; wherein at least one of R1, R2, R3, R4, and Y is alkyl. The alkyl group is, for example, methyl. The alkoxy group is, for example, methoxy. The group having an amino carbamate group is, for example, but not limited to, -OC(O)-NH-(CH2)3-, -CH2-OC(O)-NH-(CH2)3-, or -CH2-N-[CH2CH2-OC(O)-NH-(CH2)3-]2. The group having an ester group is, for example, but not limited to, -C(O)-O-CH2CH(OH)CH2-O-(CH2)3-. The group having an amino group is, for example, but not limited to, -C(O)-NH-(CH2)3-. Examples, but not limited to, (4-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate, and (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate, are also mentioned. (3-(trimethoxysilyl)propyl)carbamate, (1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)aminocarbamate {N-hexylbenzotriazole-1-carboxamide,}, etc.
[0025] <Solvent>
[0026] To ensure good workability or film-forming properties, in some embodiments of the present invention, the anti-vulcanizing adhesive further comprises a solvent. This solvent can be used alone or in combination. The solvent is, for example, but not limited to, ester solvents or alcohol solvents. Ester solvents include, for example, but not limited to, methyl acetate, ethyl acetate, butyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, ethylene glycol acetate, or diethylene glycol acetate. Alcohol solvents include, for example, but not limited to, methanol, ethanol, isopropanol, butanol, ethylene glycol, diethylene glycol, or polyethylene glycol.
[0027] The anti-sulfurization adhesive of the present invention not only has the advantages of room temperature curing and good adhesion, but also the anti-sulfurization components (such as anti-sulfurization films) formed by the anti-sulfurization adhesive have the functions of moisture protection, dust protection, chemical protection, salt spray protection, and sulfidation protection. Compared with the protective layer formed by conventional conformal adhesives, the anti-sulfurization components formed by the anti-sulfurization adhesive of the present invention also have the functions of salt spray protection and sulfidation protection.
[0028] <Products containing metal>
[0029] The present invention comprises a metal component and a sulfur-resistant member disposed on the metal component. The sulfur-resistant member is formed of a component including the aforementioned sulfur-resistant adhesive. Through the sulfur-resistant member, the metal component will not corrode due to the presence or release of sulfur in a sulfur-containing environment or when the metal-containing article has sulfur-containing elements. The metal component is, for example, but not limited to, a metal conductive line or a metal film. The metal-containing article is, for example, but not limited to, a circuit board or a keyboard. The circuit board is, for example, but not limited to, a printed circuit board. The keyboard is, for example, but not limited to, a soft keyboard or a membrane keyboard.
[0030] The present invention will be further described with reference to the following embodiments, but it should be understood that the embodiments are only for illustrative purposes and should not be construed as limiting the implementation of the present invention.
[0031] Example 1
[0032] 99.8 wt% of (meth)acrylate component, 0.12 wt% of 2,2'-azobis(isobutyronitrile) and 0.08 wt% of 1-n-dodecylthiol and butyl acetate were mixed under nitrogen atmosphere for 30 minutes to obtain a reaction mixture, wherein the (meth)acrylate component contained 84 wt% of methyl methacrylate, 6 wt% of 3-methacryloxypropyltrimethoxysilane and 10 wt% of tridecafluorooctyl methacrylate (brand: NICCA CHEMICAL CO. LTD).
[0033] The reaction mixture was then heated to 65°C and reacted at 65°C for 2 hours. Next, it was heated to 75°C and reacted at 75°C for 14 hours to obtain a silica-containing (meth)acrylate polymer with a viscosity of 200,000 cp (glass transfer temperature of 105°C and weight average molecular weight of 173,005).
[0034] Then, the silica-containing (meth)acrylate polymer is mixed with butyl acetate and isopropanol to obtain a mixture with a solid content of 10 wt%. Next, (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)aminocarbamate (abbreviated as BTA-Si-A2) is added to obtain anti-vulcanization adhesive. The preparation method of (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate involves mixing 33.3 parts by weight of (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methanol, butyl acetate, and 33.3 parts by weight of 3-isocyanatopropyltrimethoxysilane to obtain a mixture. Under nitrogen atmosphere, the mixture is heated to 60°C and stirred at 100 rpm. Then, 50 ppm of dibutyltin dilaurate is added, and the mixture is stirred at 60°C for 12 hours. Finally, the mixture is concentrated under reduced pressure at 10 mmHg and 40°C.
[0035] Examples 2 to 5 and Comparative Examples 1 to 7
[0036] The preparation of Examples 2 to 5 and Comparative Examples 1 to 7 is generally similar to that of Example 1, except that the types and amounts of the components are changed, as shown in Tables 1 and 2.
[0037] Example 6
[0038] 99.8 wt% of (meth)acrylate component, 0.12 wt% of 2,2'-azobis(isobutyronitrile) and 0.08 wt% of 1-n-dodecylthiol and butyl acetate were mixed in a nitrogen atmosphere for 30 minutes to obtain a reaction mixture, wherein the (meth)acrylate component contained 94 wt% of methyl methacrylate and 6 wt% of 3-methacryloxypropyltrimethoxysilane.
[0039] The reaction mixture was then heated to 65°C and reacted at 65°C for 2 hours, followed by heating to 75°C and reacting at 75°C for 14 hours to obtain a silica-containing (meth)acrylate polymer with a viscosity of 200,000 cp (glass transfer temperature of 100°C and weight average molecular weight of 180,500).
[0040] Then, the colloid is mixed with butyl acetate and isopropanol to obtain a mixture with a solid content of 10 wt%. Next, (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)aminocarbamate (abbreviated as BTA-Si-A2) is added to obtain anti-vulcanization adhesive.
[0041] Example 7
[0042] 99.8 wt% of (meth)acrylate component, 0.12 wt% of 2,2'-azobis(isobutyronitrile) and 0.08 wt% of 1-n-dodecylthiol and butyl acetate were mixed under nitrogen atmosphere for 30 minutes to obtain a reaction mixture, wherein the (meth)acrylate component contained 84 wt% methyl methacrylate, 6 wt% 3-methacryloxypropyltrimethoxysilane and 10 wt% tridecafluorooctyl methacrylate (brand: NICCA CHEMICAL CO. LTD).
[0043] The reaction mixture was then heated to 65°C and reacted at 65°C for 2 hours. Next, it was heated to 75°C and reacted at 75°C for 14 hours to obtain a silica-containing (meth)acrylate polymer with a viscosity of 200,000 cp (glass transfer temperature of 105°C and weight average molecular weight of 173,005).
[0044] Then, the silica-containing (meth)acrylate polymer is mixed with butyl acetate and isopropanol to obtain a mixture with a solid content of 22wt%. Next, (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)aminocarbamate (abbreviated as BTA-Si-A2) is added to obtain anti-vulcanization adhesive.
[0045] Examples 8 to 11 and Comparative Examples 8 to 13
[0046] The preparation of Examples 8 to 11 and Comparative Examples 8 to 13 is generally similar to that of Example 7, except that the types and amounts of the components are changed, as shown in Tables 3 and 4.
[0047] Example 12
[0048] 99.8 wt% of (meth)acrylate component, 0.12 wt% of 2,2'-azobis(isobutyronitrile) and 0.08 wt% of 1-n-dodecylthiol and butyl acetate were mixed in a nitrogen atmosphere for 30 minutes to obtain a reaction mixture, wherein the (meth)acrylate component contained 94 wt% of methyl methacrylate and 6 wt% of 3-methacryloxypropyltrimethoxysilane.
[0049] The reaction mixture was then heated to 65°C and reacted at 65°C for 2 hours, followed by heating to 75°C and reacting at 75°C for 14 hours to obtain a silica-containing (meth)acrylate polymer with a viscosity of 200,000 cp (glass transfer temperature of 100°C and weight average molecular weight of 180,500).
[0050] Then, the silica-containing (meth)acrylate polymer is mixed with butyl acetate and isopropanol to obtain a mixture with a solid content of 22wt%. Next, (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)aminocarbamate (abbreviated as BTA-Si-A2) is added to obtain anti-vulcanization adhesive.
[0051] Evaluation Items
[0052] The following describes the property measurement method using the anti-vulcanizing adhesive of Example 1 as an example. The other Examples 2 to 6 and Comparative Examples 1 to 7 were measured in the same manner.
[0053] Measurement of anti-sulfurization degree: The anti-sulfurization adhesive of Example 1 was applied to the silver-plated film of the substrate containing the silver-plated film by spin coating. Then, it was placed at 85°C for 5 minutes to obtain a sheet containing the substrate and a coating formed on the silver-plated film, the length and width of which were 3 cm. According to the ANSI / EIA-977 (released in 2017) method for detecting sulfur corrosion of passive components, the sheet was placed in a glass chamber with a sulfur powder concentration of 99% at the bottom. While keeping it sealed, it was placed at 105°C for 32 hours. Then, the degree of sulfurization on the appearance of the sheet was visually evaluated, and the sulfurization ratio was calculated based on the sulfurized area. The evaluation level is O: mild corrosion, with a sulfurization rate of less than 10% and a slightly yellow appearance; △: moderate corrosion, with a sulfurization rate of more than 10% but less than 30% and a grayish appearance with oxidation black spots; X: severe corrosion, with a sulfurization rate of more than 30% and a large area of blackening on the appearance.
[0054] Adhesion Measurement: The anti-sulfurization adhesive of Example 1 was spin-coated onto a substrate (copper foil or fiberglass board). The substrate was then left at room temperature for 2 hours to obtain a test sample. The test sample included the substrate and a coating formed on the substrate, with a length and width of 6 cm and 5 cm, respectively. A cross-cut tester was used to score 100 sections on the coating of the test sample. Then, 3M 600 tape was used to adhere the coating to the test sample, pressing firmly to ensure complete adhesion. The tape was then quickly removed, and the number of peeled sections was counted. The breakage ratio was then calculated based on the number of peeled sections. The evaluation grades are as follows: 0B: Damaged area is greater than 65%; 1B: Damaged area is greater than 35% but less than 65%; 2B: There is partial or large-scale peeling along the cut edge, with a damaged area greater than 15% but less than 35%; 3B: There is peeling at the cut edge and / or intersection, with a damaged area greater than 5% but less than 15%; 4B: There is small-scale peeling at the intersection of cuts, with a damaged area less than 5%; 5B: No peeling.
[0055] Salt spray resistance measurement: The following describes the measurement method of the property using the anti-vulcanizing rubber of Example 7 as an example. The other Examples 8 to 12 and Comparative Examples 8 to 13 were measured in the same manner.
[0056] The anti-sulfurization adhesive of Example 7 was spin-coated onto a copper substrate. The substrate was then left at room temperature for 10 minutes, heated to 90°C, and baked at 90°C for 2 hours to obtain a test sample. The test sample contained a copper substrate and a coating formed on the copper substrate, the coating having a thickness of 25±2 μm and a length and width of 2.5 cm. The test sample was immersed in a neutral saline solution (containing water and sodium chloride, with a sodium chloride concentration of 5 wt%) at 35°C for 48 hours. The corrosion of the copper substrate was then observed, and the percentage of corroded area was calculated as a representation of the degree of corrosion.
[0057] The following describes the property measurement method using the anti-vulcanizing adhesive of Example 1 as an example. The other Examples 2 to 12 and Comparative Examples 1 to 13 were measured in the same manner.
[0058] Moisture barrier performance measurement: The anti-sulfurization adhesive of Example 1 was applied to a nylon mesh (400 mesh, 10cm long and wide) using a scraper. After being left at room temperature for 24 hours, a film with a thickness of 0.5mm was obtained. According to the ASTM E96 moisture permeability test standard method (published in 2016), white anhydrous copper sulfate was placed in a permeation cup. Then, a gasket, the film, a metal ring, and a fixing valve were stacked sequentially on the rim of the permeation cup. 2 ml of water was dropped onto the film and left to stand at room temperature for 48 hours. The color change of the anhydrous copper sulfate in the permeation cup was then observed visually. O indicates that the anhydrous copper sulfate remains white and has a moisture-proof function; X indicates that the color of the anhydrous copper sulfate changes from white to blue and no longer has a moisture-proof function. It should be noted that since water vapor can be blocked by the membrane, it can be reasonably inferred from the general knowledge of the size of water vapor and dust that dust, such as particulate matter, can also be blocked by the membrane. Therefore, the membrane also has a dustproof function.
[0059] Chemical barrier property measurement: The anti-sulfurization adhesive of Example 1 was coated onto a nylon mesh (400 mesh, 10 cm long and wide) using a scraper. After being left at room temperature for 24 hours, a film with a thickness of 0.5 mm was obtained. According to the ASTM E96 moisture permeability test standard method (published in 2016), white starch was placed in a permeation cup. Then, a gasket, the film, a metal ring, and a fixing valve were stacked sequentially on the mouth of the permeation cup. 2 ml of concentrated sulfuric acid was dropped onto the film, and the mixture was left to stand at room temperature for 48 hours. The color change of the starch in the permeation cup was then observed visually. O indicates that the starch remains white and has chemical barrier properties; X indicates that the starch changes from white to black and no longer has chemical barrier properties.
[0060] Table 1 Example 1 2 3 4 5 6 reaction mixture Methyl methacrylate (wt%) 84 84 84 84 84 94 3-Methylpropenoxypropyltrimethoxysilane (wt%) 6 6 6 6 6 6 Tridecafluorooctyl methacrylate (wt%) 10 10 10 10 10 0 2,2'-Azobis(isobutyronitrile) (wt%) 0.12 0.12 0.12 0.12 0.12 0.12 1-n-Dodecanethiol (wt%) 0.08 0.08 0.08 0.08 0.08 0.08 Mixture Solid content (%) 10 10 10 10 10 10 BTA-Si-A2 (wt%) 0.5 1 2 3 5 2 1-Methylbenzotriazole (wt%) 0 0 0 0 0 0 N-Phenyl-3-aminopropyltrimethoxysilane (wt%) 0 0 0 0 0 0 Evaluation Project Adhesion Coating thickness (μm) 4~5 5~6 5~6 5~6 5~6 4~5 copper foil 4B 4B 5B 5B 5B 4B Fiberglass board 4B 4B 4B 4B 4B 5B Degree of anti-sulfurization Percentage of sulfurized products (%) 5 0 0 0 3 0 evaluate O O O O O O Water vapor barrier O O O O O O Chemical barrier O O O O O O
[0061] Table 2 "--": Not measured Comparative example 1 2 3 4 5 6 7 reaction mixture Methyl methacrylate (wt%) 84 84 84 84 84 84 84 3-Methylpropenoxypropyltrimethoxysilane (wt%) 6 6 6 6 6 6 6 Tridecafluorooctyl methacrylate (wt%) 10 10 10 10 10 10 10 2,2'-Azobis(isobutyronitrile) (wt%) 0.12 0.12 0.12 0.12 0.12 0.12 0.12 1-n-Dodecanethiol (wt%) 0.08 0.08 0.08 0.08 0.08 0.08 0.08 Mixture Solid content (%) 10 10 10 10 10 10 10 BTA-Si-A2 (wt%) 0 0.4 6 8 10 0 0 1-Methylbenzotriazole (wt%) 0 0 0 0 0 0 2 N-Phenyl-3-aminopropyltrimethoxysilane (wt%) 0 0 0 0 0 2 0 Evaluation Project Adhesion Coating thickness (μm) 4~7 4~5 4~6 4~6 5~6 6 4~6 copper foil 0B 1B 2B 1B 1B 0B 5B Fiberglass board 0B 2B 2B 1B 3B 4B 3B Degree of anti-sulfurization Percentage of sulfurized products (%) 40 60 50 -- 100 15 70 evaluate X X X -- X △ X Water vapor barrier O O O O O O O Chemical barrier O O O O O O O
[0062] Referring to Tables 1 and 2, it can be seen from Examples 1 to 6 that the coating formed by the anti-sulfurization adhesive of the present invention containing BTA-Si-A2 does indeed achieve an anti-sulfurization effect on the silver-plated film of the substrate. In contrast, the coatings of Comparative Examples 1 to 7 do not contain BTA-Si-A2 or the content of BTA-Si-A2 contained in Comparative Examples 1 to 7 is not in the range of 0.5wt% to 5wt%, and the coating formed by the coating cannot achieve a good anti-sulfurization effect on the silver-plated film of the substrate. As can be seen from the above, the anti-sulfurization adhesive of the present invention does indeed have a good anti-sulfurization effect.
[0063] Table 3 Example 7 8 9 10 11 12 reaction mixture Methyl methacrylate (wt%) 84 84 84 84 84 94 3-Methylpropenoxypropyltrimethoxysilane (wt%) 6 6 6 6 6 6 Tridecafluorooctyl methacrylate (wt%) 10 10 10 10 10 0 2,2'-Azobis(isobutyronitrile) (wt%) 0.12 0.12 0.12 0.12 0.12 0.12 1-n-Dodecanethiol (wt%) 0.08 0.08 0.08 0.08 0.08 0.08 Mixture Solid content (%) twenty two twenty two twenty two twenty two twenty two twenty two BTA-Si-A2 (wt%) 0.5 1 2 3 5 2 1-Methylbenzotriazole (wt%) 0 0 0 0 0 0 N-Phenyl-3-aminopropyltrimethoxysilane (wt%) 0 0 0 0 0 0 Evaluation Items Degree of corrosion (%) 0 0 0 0 0 0 Water vapor barrier O O O O O O Chemical barrier properties O O O O O O
[0064] Table 4 Comparative example 8 9 10 11 12 13 reaction mixture Methyl methacrylate (wt%) 84 84 84 84 84 84 3-Methylpropenoxypropyltrimethoxysilane (wt%) 6 6 6 6 6 6 Tridecafluorooctyl methacrylate (wt%) 10 10 10 10 10 10 2,2'-Azobis(isobutyronitrile) (wt%) 0.12 0.12 0.12 0.12 0.12 0.12 1-n-Dodecanethiol (wt%) 0.08 0.08 0.08 0.08 0.08 0.08 Mixture Solid content (%) twenty two twenty two twenty two twenty two twenty two twenty two BTA-Si-A2 (wt%) 0 0.4 6 0 0 0 1-Methylbenzotriazole (wt%) 0 0 0 0 1 2 N-Phenyl-3-aminopropyltrimethoxysilane (wt%) 0 0 0 2 0 0 Evaluation Project Corrosion degree (%) 20 16 16 17 14 15 Water vapor barrier O O O O O O Chemical barrier O O O O O O
[0065] Referring to Tables 3 and 4, it can be seen from Examples 7 to 12 that the coating formed by the anti-sulfurization adhesive of the present invention containing BTA-Si-A2 does indeed achieve the effect of preventing salt spray on copper substrates. In contrast, the coatings of Comparative Examples 8 to 13 do not contain BTA-Si-A2 or the content of BTA-Si-A2 contained in Comparative Examples 8 to 13 is not in the range of 0.5wt% to 5wt%, and the coatings formed by these coatings cannot achieve the effect of preventing salt spray on copper substrates. As can be seen from the above, the anti-sulfurization adhesive of the present invention not only has the effect of preventing sulfidation but also has the effect of preventing salt spray.
[0066] However, the above description is only an embodiment of the present invention and should not be construed as limiting the scope of the present invention. Any simple equivalent changes and modifications made in accordance with the scope of the patent application and the contents of the patent specification shall still fall within the scope of the patent of the present invention.
Claims
1. An anti-vulcanizing adhesive, comprising: a (meth)acrylate polymer having silicate groups, formed by polymerization of a reaction mixture, wherein the reaction mixture comprises a (meth)acrylate component and a thermal initiator, wherein, The (meth)acrylate component includes a silicate monomer and 80 wt% to less than 100 wt% of an alkyl (meth)acrylate, the amount of the thermal initiator being 0.05 wt% to 1.0 wt% based on a total reaction mixture of 100 wt%; and 0.5 wt% to 5 wt% of a benzotriazole molecule having a silicate group.
2. The anti-vulcanizing adhesive as described in claim 1, wherein, The benzotriazole molecule with a silicate group is defined as follows: R1, R2, R3, and R4 are independently hydrogen, alkyl, or alkyl; Y represents hydrogen or alkyl; L is a group having an aminocarbamate group, an ester group, or an amino group; T1 to T3 are independently hydrogen or alkoxy; T1 to T3 are not simultaneously hydrogen; n represents an integer greater than 1; wherein at least one of R1, R2, R3, R4, and Y is alkyl.
3. The anti-vulcanizing adhesive as described in claim 1, wherein, The benzotriazole molecule with a silicate group is selected from (4-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate, (5-methyl-1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate, (1H-benzo[d][1,2,3]triazol-1-yl)methyl(3-(trimethoxysilyl)propyl)carbamate, etc., or combinations thereof.
4. The anti-vulcanizing adhesive as described in claim 1, wherein, The siloxane monomer is selected from vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, dimethoxymethylvinylsilane, diethoxymethylvinylsilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, or any combination thereof.
5. The anti-vulcanizing adhesive as described in claim 1, wherein, The (meth)acrylate component also includes fluorinated alkyl (meth)acrylates.
6. The anti-vulcanizing adhesive as described in claim 5, wherein, The fluorinated alkyl ester of (meth)acrylate is selected from dodecafluoroheptyl acrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl acrylate, tridecafluorooctyl methacrylate, heptadecafluorodecyl acrylate, heptadecafluorodecyl methacrylate, or any combination thereof.
7. The anti-vulcanizing adhesive as described in claim 5, wherein, Based on a total amount of 100 wt% for the (meth)acrylate component, the amount of the fluorinated alkyl methacrylate is greater than 0 wt% and less than 15 wt%.
8. The anti-vulcanizing adhesive as claimed in claim 1, wherein, The reaction mixture also contains a chain transfer agent.
9. The anti-vulcanizing adhesive as described in claim 8, wherein, Based on a total reaction mixture of 100 wt%, the amount of the chain transfer agent is greater than 0 wt% and less than 1.0 wt%.
10. An article having metal components, comprising a metal member and a sulfur-resistant component disposed on the metal member, wherein, The anti-vulcanization component is formed from a component comprising an anti-vulcanization adhesive as described in any one of claims 1 to 9.